Multiple paradoxical embolisms revealing a patent foramen ovale in a patient with deep venous thrombosis: A case report. (June 2021) - Banana, Youssef; Rezziki, Abdellah; Kallel, Oussama; Rasras, Hammam; Bazid, Zakariae; El Ouafi, Noha; El Mahi, Omar; Benzirar, Adnane
Abstract: Introduction: Paradoxical embolism is a rare medical phenomenon. Depending on the site of embolisation, it can cause different symptoms. Although rare, mesenteric ischemia can reveal paradoxical embolism, and the embolisation of two different sites is rarely described in the literature. Case presentation: We report the observation of a patient with a table associating an acute mesenteric ischemia and an acute ischemia of the upper limb; whose the etiological assessment revealed a deep venous thrombosis of the lower limbs complicated by pulmonary embolism. Clinical discussion: These paradoxical embolisms occurred through a patent foramen ovale. The diagnosis of the patent foramen ovale in this patient was revealed by transthoracic echocardiography, with bubble test. The patient benefited from an embolectomy of the superior mesenteric artery and an embolectomy using fogarty catheter by approching humeral artery at the elbow crease with good postoperative evolution. The patient was put on long-term anticoagulation with Acenocoumarol (because of low socio-economic level of our patient). We didn't recommended the closure of the PFO because of the small size of the shunt and especially because the patient refuses that procedure. Conclusion: Paradoxical embolism remains a pathology rarely mentioned by clinicians, although it can engage the functional and vital prognosis of the patient, hence the interest of a good cardiac evaluation in any patient with embolic ischemia. Highlights: PFO is most often asymptomatic but it can cause manifestations with variable degrees of severity. If it is not earyl diagnosed, or negligated, it can be life-threatining Paradoxical embolism is a pathological condition that requires a multidiscplinary management.